Intraventricular Meningioma: A Case Series - Valentino, Andrea; Wahyudi; Prastya Pardede, Jeremia; Maspian Tjili , Tondi; Hadisi, Anthar; Aji Prihartomo, Gatot; Wirdayanto, Ade; Rangkuti, Ina Farida (Surgical Residency Program Syiah Kuala University, 2024)
Introduction: Intraventricular meningiomas account for approximately 1.5% of meningiomas, 80% of these were localized in the lateral ventricles, 15% in the third ventricle (mostly in the ventricle trigone), and the remaining 5% in the fourth ventricle. This case report aims to highlight clinical findings and difficulty on removal of the tumor intraoperatively. Case description: We presented 2 cases of Intraventricular Meningioma. Both patient have a chief complaint of chronic headache since 2 years ago. Through the magnetic resonance imaging examination, we found a solid mass at right ventricle trigone with enhance homogenously 7.3 x 5.5 x 6.5 cm on the first patient and 6.8 x 8.4 x 3.2 cm on the second patient. Both patients went through craniotomy tumor removal. The pathology showed a Transitional Meningioma who grade I and KI-67 immunohistochemical staining result: 1-2 % on the first patien and angiomatous meningioma (WHO grade 1) on the second patient. Both patients showed improvement post-surgery Conclusion: We have successfully performed a total craniotomy tumor removal on the right trigone intraventricular meningioma. However, the primary challenge lies in excising intraventricular meningiomas located in the trigone without causing injury to the geniculocalcarine tracts. Therefore, the surgical approach must be carefully planned based on the tumor's location and intraoperative monitoring as well as surgical strategy to avoid the neurological deficits.